PENGARUH MODEL PEMBELAJARAN COOPERATIVE SCRIPT TERHADAP KEMAMPUAN MENGANALISIS TEKS NEGOSIASI SISWA KELAS X SMA NEGERI 1 PARUNGKUDA - Aurelya, Aurelya Ramadhanty; Ahmad Supendi, Deden; Humaira, Hera Wahdah (JURNAL SKRIPTA, 2025)
The observation results showing the low analytical skills of students make this research necessary to obtain results that the use of the Cooperative Script model has a significant impact on improving the ability to analyze negotiation texts of students in class X. SMA Negeri 1 Parungkuda is the place chosen to conduct the research. Two sample classes were randomly selected for research materials. The method used is quantitative with a True Experimental Design research design, especially the Posttest Only Control Group Design. To analyze the data, the Independent Samples t-test was used as a hypothesis test, which aims to compare the Cooperative Script learning model with conventional learning methods. This comparison is made by considering the average value (mean) of the two sample classes. The results of the Independent Sample t-test show a significance value (2-tailed) of 0.000 <0.05, thus, H0 is rejected and H1 is accepted. From these results, it indicates that the Cooperative Script learning model has a significant impact on improving the analytical skills of negotiation texts of class X students at SMA Negeri 1 Parungkuda. Keywords: Learning Outcomes, Learning Models, Cooperative Script.